Landslide susceptibility of Rwanda (Central Africa) - Cristian Panelli; Vincenzo Marsala; Giorgio Paglia; Alberto Galli; Paride Colasante; Enrico Miccadei (Journal of Maps)
This paper presents a novel landslide susceptibility map of Rwanda (Central Africa), sadly acknowledged as highly exposed to natural hazards and affected by recurring landslide phenomena. The susceptibility assessment was performed using an integrated approach based on morphometric analysis in a Geographic Information System (GIS), supported by orthophoto analysis and geomorphological field mapping. The analysis was completed following a heuristic approach; 10 landslide controlling parameters were identified. Each parameter was assigned an appropriate weight based on expert judgement and analysed to realize thematic maps. All the data collected were mapped through a process of cartographic overlap to carry out the final zonation. The resulting map was grouped into five susceptibility classes (very low, low, medium, high, and very high), identifying areas with different probabilities of being affected by landslides. The Main Map represents a valuable tool to support sustainable territorial planning and landslide hazard assessment.